IMPROVEMENT OF PRODUCT QUALITY THROUGH SIX SIGMA AND FUZZY MARKETING MIX APPROACHES - Maria Ulfah; Faula Ariana; Dyah Lintang Trenggonowati (Department of Agroindustrial Technology, Bogor Agricultural University, 2021)
According to 2019 annual sales data, the amount of Baros 19-liter bottled water sales experienced 26,304 units drop. The objective of this research was to determine the score-gap of each quality attributes of the product according to Fuzzy Marketing Mix method; to determine the Sigma achievement level on the quality of the product; to determine attributes of product quality that needed to be improved in cartesian diagram; to identify various factors that affect the consumer’s unsatisfaction at the attribute with highest negative score and DPMO; and to provide constructive analysis on product quality improvement according to Fuzzy FMEA method. The Six Sigma approach was done through DMAIC steps, which were define, measure, analyze, improve, and control. The result from the define step, which was mapping of attribute dimensions Marketing Mix 4P was 27 attributes and voice of customer measurement was done with 100 respondents. In measure step, it was found that the biggest negative discrepancy, with the value of -0.4452, was between satisfaction and importance which was found in attribute 23. In measure step, it was also found that the average Sigma score of bottled water in Indonesia is 2.561 with average DPMO of 153,204. In the analyze step, root cause identification of the attribute with highest negative discrepancy, which was delay in product delivery to the consumers (attribute 23), was done. Improvements that can be done to increase the product quality of 19-liter bottled water was to ensure availability of new water bottle for every driver lacking empty bottle. Keywords : DPMO; Fuzzy; Marketing Mix; Quality; Six Sigma